Analysis of the national ideology formation of future music teachers - Пащенко, Інна Миколаївна (Pedagogy of Higher and Secondary Education, 2015)
Paschenko I. N. Analysis of the national ideology formation of future music teachers. The article presents the cuttent results of national ideology formation of future music teachers. The criteria and indicators of the national ideology formation were analyzed and the levels of its formation in the framework of the ascertaining experiment were determined.